Environmental Literature Capabilities of Students In Class IV of Interpated Islamic Elementary School El-Haq Sidoarjo Reviewing From Knowledge, Attitude, and Behavior: Kemampuan Literasi Lingkungan Siswa Kelas IV Sd Islam Terpadu El-Haq Sidoarjo Ditinjau Dari Pengetahuan, Sikap, dan Perilaku - Fachriyatul Ifadah; Kemil Wachidah (Universitas Muhammadiyah Sidoarjo, 2022)
Environmental literacy is an ability in the process of environmental education to determine the ability of awareness which aims to understand the conditions of environmental issues based on knowledge, attitudes, and behavior. Environmental education is one of the important factors for success in instilling character values ​​with environmental culture. Therefore, this study aims to measure the environmental literacy skills of fourth grade students of SD Islam Terpadu El-Haq Sidoarjo in terms of knowledge, attitudes, and behavior. This study used a qualitative descriptive approach with a phenomenological method by collecting data through tests, questionnaires, and written documentation which were then checked for correctness using technical triangulation. The results showed that (1) the students 'knowledge of the environment was classified as very good, (2) the students' attitude towards the environment was classified as very good, (3) the caring behavior towards the environment was classified as very good.